(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
Diabetic polyneuropathy (DPN) is the most prevalent and disabling chronic complication of diabetes, greatly increasing the risks of foot ulceration, amputation, and cardiovascular morbidity. Traditional treatment—primarily focused on glycemic control and symptomatic pain relief—has shown limited ability to reverse or halt the progression of neuropathy. This review highlights the need for a modern, integrated therapeutic strategy that combines optimized endocrinological management with innovative, pathogenesis-targeted neurological interventions. We explore recent systemic advances, including the metabolic benefits of newer antidiabetic agents such as SGLT2 inhibitors and GLP-1 receptor agonists, as well as the importance of addressing cardiovascular risk factors that contribute to nerve ischemia. Additionally, we discuss emerging disease-modifying therapies, including alpha-lipoic acid, VM202 gene therapy, and high-frequency spinal cord stimulation (SCS). Early detection methods such as Corneal Confocal Microscopy offer promising potential for identifying neuropathy before irreversible damage occurs. A comprehensive, personalized treatment strategy uniting metabolic optimization with advanced neurological therapies offers the greatest opportunity to achieve meaningful clinical improvement and enhance quality of life for patients with DPN. [1]